Probiotics for inflammatory bowel diseases: a promising adjuvant treatment. (2nd January 2019) - Coqueiro, Audrey Y.; Raizel, Raquel; Bonvini, Andrea; Tirapegui, Julio; Rogero, Marcelo M.
Abstract: Inflammatory bowel diseases (IBD) encompass ulcerative colitis (UC), Crohn's disease (CD) and indeterminate colitis (IC), characterising chronic inflammation in the gastrointestinal tract, associated with changes in the immune system and in the intestinal microbiota. Thus, probiotics may offer an alternative or adjuvant approach to conventional therapy. The present review aims to summarise the mechanisms of action of probiotics in IBD and their therapeutic effects. Most of the studies suggest that probiotics are effective in the treatment of UC, especially when several strains are concomitantly administered. Species of Lactobacillus and Bifidobacterium genres are the most commonly used, and some studies even indicate that it is possible to replace medical therapy with probiotic supplementation. Regarding CD, the results of clinical trials are controversial and do not support the use of probiotics in this disease. In conclusion, probiotic supplementation is a promising adjuvant treatment in UC, but not in CD.